Determinação das causas de morte e descarte dematrizes suínas em granja de sistema intensivo de criação - Matias, Débora Novais (2020)
The sow mortality representes a bottleneck in the swine female, reflecting in the entire production chain. The mortality rate considers females of reproductive age who died spontaneously or were euthanized within the farm installations. In this work, were obtainedepidemiological data, the macroscopic and histopathological findings weredescribed andwere associated with the main causes of mortality in sows and the reason that lead to their discard. The lesions observed at necropsy,were described, samples of tissues were collected andfixed in 10% formaldehyde, processed for histology and stained with hematoxylin and eosin, according to the routine of the Veterinary Pathology Sector of the Federal University from Lavras. In the collection period (March to May 2019) 134 necropsies of sows were performed, 110 of which met the insertion criteria, obtaining 414 histological slides. Regarding the epidemiological data of sows, the production site in which they were inserted, the stage of the production cycle at the time of death, the type of accommodation, the type of death, the body score and the farrowing order were considered. The diagnoses were classified according to the main organ and system affected, with a predominance of disorders of the genitourinary system (31%), followed by the digestive (25%), locomotor (21%), respiratory (5%) and cardiovascular (3%) systems; deaths that were not associated to these systems were arranged in the cause ‘others’, which represented 15%. The necropsy associated with histopatology were essential to final diagnose. Factors related to ambience and labor had a significant impact on the causes of sow mortality.